Understanding how multinational enterprises manage global supply chains during major geopolitical disruptions: the role of structural ambidexterity - Moradlou, Hamid; Skipworth, Heather; Bals, Lydia; Aktas, Emel; Roscoe, Sam (Emerald, 2023)
This paper seeks insights into how multinational enterprises restructure their global supply chains to manage the uncertainty caused by geopolitical disruptions. Evidence is gathered from 29 interviews with senior executives working for 14 multinational companies affected by Covid-19, the US-China Trade War and Brexit. To manage this uncertainty, we find that companies implement structural ambidexterity in supply chains by partitioning internal subunits, reconfiguring supplier networks, and creating parallel supply chains. The findings contribute to Dunning’s eclectic paradigm by explaining how organisational ambidexterity is extended beyond firm boundaries and embedded in global supply chains to mitigate uncertainty and gain exploration and exploitation benefits.
Keywords: Supply chain design; ambidexterity; organizational learning theory